Empowering the undergraduate journey: A decade of research on the impact of life coaching with university students - Levi Huffman; Erin M. Lefdahl-Davis; Alexandra Alayan; Daphne Washington (International Journal of Evidence Based Coaching and Mentoring)
At many institutions of higher learning, counseling resources are provided for students, yet professional coaching services are rare. This study (which continued a 3-year study on coaching outcomes published in 2018) details the outcomes of providing professional life coaching to undergraduates with 10 years of quantitative and qualitative data (Lefdahl-Davis et al., 2018). Undergraduate students who received life coaching reported increased self-confidence, greater connection to life purpose, satisfaction with choice of major, awareness of values and alignment with decision making, and help with individual goal setting and attainment. After receiving coaching, diverse students reported even greater gains than white students in efficacy (alignment of values with decisions), confidence in life purpose, and confidence in choice of major. This mixed-methods study reveals significant evidence that providing professional life coaching to undergraduates can be a highly effective method to develop young adults, enhance retention, and increase well-being and life satisfaction.